Investigation of air-flow accelerators of tower type for wind power plants with vertical axis of rotation - А. А. Bubenchikov; Т. V. Bubenchikova; E. N. Eremin; V. V. Kharlamov (Омский научный вестник)
The work is aimed at determining the geometric parameters of the concentrator for maximum acceleration of the air flow passing through it. The article presents design variants of a tower-type accelerator from a simple design to a complex one with the addition of additional structures allowing to exclude tearing and unwanted twisting of the air flow in the channel body.